Using marine deposits to understand terrestrial human environments: 6000-year old hyperpycnal flash-flood events and their implications. (April 2020) - Farr, R. Helen; Clapham, Alan; Reinhardt, Eduard G.; Boyce, Joseph I.; Collins, Shawn; Robb, John
Highlights: Excellent preservation of organic deposits in offshore setting. Utility of secondary deposits for understanding palaeolandscape and enriching the onshore archaeological record. Long record of flash-flooding on the southern Italian coast that dates back to prehistory. Abstract: Offshore sedimentary deposits preserved in submarine canyons in southern Calabria, Italy, provide evidence for mid-Holocene (ca. 6000 BP) erosion and the transport of organic-rich floodplain sediments by flash-flood (hyperpycnal) flows from the San Pasquale River. Marine geophysical surveys (bathymetry, side-scan sonar) and diver reconnaissance revealed an unusual offshore peat deposit containing plant macrofossils representing local habitats, potentially reflecting human modified landscapes. The 20–30 cm thick organic deposit included a large tree trunk, well-preserved seeds, leaves, sticks and other delicate organics. Textural and microfossil (foraminifera) analysis of associated sediments (sands and muds) indicate that these deposits resulted from hyperpycnal flood events that were deposited as sediment gravity flows within gullies on the canyon margins. Whilst the value of studying in situ submerged prehistoric landscapes is well documented, we demonstrate that reworked floodplain deposits preserved in offshore environments can provide useful palaeoenvironmental information that may not be preserved in terrestrial settings. The botanic archive preserved in submarine flood deposits at San Pasquale affords a unique insight into the local environment in which people lived during the Final Neolithic.